Digital Transformation of MSMEs: Navigating Opportunities and Challenges in the Industry 4.0 Era - Stanss. L. H. V. Joyce Lapian; Silvya L. Mandey; Willem J. F. A. Tumbuan; Imelda W. J. Ogi; Roberthair Suripatty; Winarsih Winarsih; Meiland Makalisang; Naomi Ormak (Univiversitas Dr. Djar Wattiheluw, 2025)
This study explores the opportunities and challenges MSMEs face in adopting digital technologies during the Fourth Industrial Revolution. While digital platforms offer benefits like improved efficiency, broader market access, and innovation, MSMEs encounter challenges such as poor infrastructure, limited digital skills, financial limitations, and cybersecurity concerns. The study suggests solutions including ongoing digital training, infrastructure improvements, better financing access, and enhanced cybersecurity awareness to help MSMEs navigate digital transformation, boost competitiveness, and ensure sustainability in the digital economy.